2021
DOI: 10.1038/s41419-021-03849-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor induces mammary tumorigenesis through prolactin/p-STAT5 pathway

Abstract: Oxytocin receptor (OXTR) is involved in social behaviors, thermoregulation, and milk ejection, yet little is known about its role in breast cancer. To investigate the role of OXTR in mammary gland development and tumorigenesis, a transgenic mouse model of OXTR overexpression (++Oxtr) was used. Overexpression of OXTR-induced progressive mammary hyperplasia, unexpected milk production, and tumorigenesis in females. OXTR-induced mammary tumors showed ERBB2 upregulation and mixed histological subtypes with predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…This hypothesis is supported by a mouse study using MDA-MB-231 cells, where the OTR levels were higher in metastasised tumour cells than in the corresponding primary xenograft tumour cells ( Figure 2 C) [ 27 ], as well as by this study’s transwell migration assays, where selected and amplified migrated T2 and T4 cells had ~2.1-fold and ~2.5-fold higher OTR expression than the parental control cells cultured in normal medium with 10% FBS ( Figure 2 B). These results align well with recent findings in a transgenic mouse model of OTR overexpression where OTR overexpression in the tumour microenvironment promotes mammary-specific tumour growth and metastasis [ 57 ]. Patients with metastatic TNBC usually have short progression-free survival (median 3–4 months) after the failure of first-line chemotherapy [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis is supported by a mouse study using MDA-MB-231 cells, where the OTR levels were higher in metastasised tumour cells than in the corresponding primary xenograft tumour cells ( Figure 2 C) [ 27 ], as well as by this study’s transwell migration assays, where selected and amplified migrated T2 and T4 cells had ~2.1-fold and ~2.5-fold higher OTR expression than the parental control cells cultured in normal medium with 10% FBS ( Figure 2 B). These results align well with recent findings in a transgenic mouse model of OTR overexpression where OTR overexpression in the tumour microenvironment promotes mammary-specific tumour growth and metastasis [ 57 ]. Patients with metastatic TNBC usually have short progression-free survival (median 3–4 months) after the failure of first-line chemotherapy [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…The STAT5 activation in tumor macrophages by derived factors from breast cancer cells led to the expression of anti-tumor immune stimulatory genes [50]. On the other hand, it was shown that STAT5a, an isoform of STAT5, could confer resistance to doxorubicin [51] and combined PI3K/mTOR and JAK2/STAT5 pathways inhibition induced cell death in triple-negative breast cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the down-regulation of the OXTR gene expression was reported recently in breast cancer relative to the non-cancer tissue [ 140 , 141 ]. In contrast, mammary tumorigenesis was induced by the overexpression of OXTR in a mouse model [ 142 ].…”
Section: Oxtr In Cancermentioning
confidence: 99%